Report of the Auditor of Public Accounts, showing the aggregate number of persons returned delinquent by the sheriffs of the Commonwealth, for the non-payment of taxes for 1860; also the aggregate amount of such taxes (LLMC-digital (Series), 1861)
Contains the report of the Auditor of Public Accounts showing the aggregate number of delinquent persons found by the Virginia sheriffs for nonpayment of taxes in 1860, as well as the aggregate amount owed. The table was arranged by counties and listed delinquencies for both personal property and capitation taxes. The report was signed by the Auditor of Public Accounts, and dated March 1, 1861 in Richmond, Va.